2014
DOI: 10.1186/1756-0500-7-719
|View full text |Cite
|
Sign up to set email alerts
|

Emerging scrub typhus infection in the northern region of Sri Lanka

Abstract: BackgroundThere is an increasing trend in rickettsioses or typhus fevers in the island of Sri Lanka. The seroepidemiological mapping previously published did not include the northern region of the island. This study was conducted to demonstrate the presence of scrub typhus (ST) and to characterise the clinical presentation of ST in this region.FindingsSerum samples from patients (n = 64) with clinical symptoms suspected of typhus fever following exclusion of other common febrile illnesses commonly seen in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
2
11
1
Order By: Relevance
“…Rickettsial infections have re-emerged in Sri Lanka with predominance of spotted fever group (SFG) in the central hills [ 1 8 ]. Even though, clinical picture of the infection is typical in many situations, variations have been reported [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rickettsial infections have re-emerged in Sri Lanka with predominance of spotted fever group (SFG) in the central hills [ 1 8 ]. Even though, clinical picture of the infection is typical in many situations, variations have been reported [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 The Northern Province has a predominance of scrub typhus. 24 However, an outbreak attributed to spotted fever, diagnosed by sero-positivity to Rickettisa conorii using IFA has been reported from army personnel within the Kilinochchi area from October to December 2012. 25 Premaratne et al reported that while scrub typhus was the predominant rickettsioses found among army personnel deployed in the Northern Province presenting with an acute febrile illness, the majority of apparently healthy army personnel had serological evidence of exposure to spotted fever.…”
Section: Geographical Distribution Of Rickettsioses In Sri Lankamentioning
confidence: 99%
“…21,34 Eschar is rarely associated with spotted fever. 18,21,24 However, in the outbreak of rickettsioses in the Kilinochchi area mentioned above, a considerable proportion of patients with serological evidence of spotted fever had demonstrated an eschar like lesion, particularly in the eye. 25 The rash in spotted fever is typically a macular papular rash.…”
Section: Clinical Presentation Of Rickettsiosesmentioning
confidence: 99%
“…It is estimated that one million cases of ST were found each year within this region, and at least one billion people are at risk of becoming infected 12,13 . Moreover, the incidence in all known endemic regions has begun to rise over the last decade [14][15][16][17] . Recent evidence from China indicated that ST has expanded to all the provinces across both rural and urban areas, and the incidence of ST has increased in an unprecedented manner, in both historically endemic areas and in new areas not previously identi ed as having cases 18 .…”
Section: Introductionmentioning
confidence: 99%